Closure - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2023)
Journal of Infrastructure & Facility Asset ManagementVolume 4, Issue 1, April 2022                                       (e) ISSN 2656-8896  (P) ISSN 2656-890XJIFAM, Vol.4, Issue 2, August 2022Comparison of Embankment Reinforcement Requirements with Geotextile on Soft Soil with 2D and 3D Slope Stability Analysis Methods  Nur Arfiati Shoffiana, Yudhi Lastiasih & Trihanyndio Rendy Satrya      Evaluation of Smart Mobility Indicators in Responding COVID-19 Pandemic in Indonesia             Shanty Y. Rachmat & Ganesha G. MangkoesoebrotoGeotechnical Mapping for Soil Physical and Mechanical Parameters and Hard Soil Depth in  Badung Regency            Zefira Wisna Maulidha, Trihanyndio Rendy Satrya & Yudhi Lastiasih      Evaluating COVID-19 Transmission Prevention Measures in Public Rental Flats (Rusunawa)            Rosyidah ‘Adilah, Prananda NavitasThe adequacy of Public Bus Fleet during the Covid-19 Pandemic (Case of The Transjakarta Corridor 1 DKI Jakarta, Indonesia)             Amanda Dian W.Kusumawardani, Ibnu Syabri, Fika Novitasari & Naya C. Drestalita